Muslim Experiential Religiousness: Relationships with Attitude toward Islam, Religious Reflection, and Basic Needs Satisfaction in Iranians - Ghorbani, Nima (Research in the social scientific study of religion, 2014)
Iranian seminarians and general university students responded to a Muslim Experiential Religiousness measure of Islamic spirituality. This instrument correlated positively with the Attitude toward Islam Scale, two types of Islamic Religious Reflection, Afterlife Motivation, and Basic Needs Satisfaction. Muslim Experiential Religiousness also displayed an ability to mediate and moderate at least some Attitude toward Islam relationships with other measures. Seminary students scored higher than general university students on Muslim Experiential Religiousness, and multiple mediation analyses revealed that Muslim Experiential Religiousness supplemented the Attitude toward Islam Scale in explaining some differences displayed by these two student groups. These data most importantly illustrated how Muslim Experiential Religiousness made it possible to analyze the role of spirituality in actualizing the adaptive religious and psychological potentials of Islam.